2018
DOI: 10.4028/www.scientific.net/msf.931.608
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Specific Properties and Features of Application of New Industrial High-Damping Steel

Abstract: Mechanical, damping and specific properties of new structural high-damping steel have been studied in the present research. Studied high-damping steel was specially produced by the JSC Severstal in order to obtain metallic material with specified level of damping and mechanical properties. Experiments show that the damping properties of industrial high-damping steel are comparable with damping properties of high-purity damping alloys, produced using laboratory equipment. Mechanical properties of the industrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Fe–Al alloys have good damping properties due to magneto-mechanical decay of mechanical vibrations in the Hz range of loading. All studied alloys [ 88 , 89 , 90 ] were forged, hot rolled, and annealed in high-vacuum furnaces. The maximal damping capacity of the Fe–Al alloys was recorded in the concentration range between 5.5 and 6.2 wt.% of Al, although maximum magnetostriction is observed in the range of 9–12 wt.% Al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fe–Al alloys have good damping properties due to magneto-mechanical decay of mechanical vibrations in the Hz range of loading. All studied alloys [ 88 , 89 , 90 ] were forged, hot rolled, and annealed in high-vacuum furnaces. The maximal damping capacity of the Fe–Al alloys was recorded in the concentration range between 5.5 and 6.2 wt.% of Al, although maximum magnetostriction is observed in the range of 9–12 wt.% Al.…”
Section: Introductionmentioning
confidence: 99%
“…High damping in the Fe–Al alloys has practical importance. It was proved [ 90 ] that high damping capacity can be achieved not only in the high-purity laboratory Fe–Al alloys but also in alloys produced using modern highly efficient metallurgical equipment with a heal volume as large as 350 tons. This industrial Fe–Al alloy was found to exhibit high damping, good mechanical properties, and low manufacturing cost [ 90 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation